Citizenship Education in The Character Building of The Nation - Bambang Yuniarto; Rivo Panji Yudha (International Journal of Education and Humanities, 2021)
The reason for this examination is to discover the job of urban instruction in molding the individual person. Up to this point, our learning has been verbal, and is just arranged towards dominating the substance of urban training subjects. Perception of every day learning practice shows that the focal point of learning is to allow understudies to dominate the data contained in the subject, and afterward evaluate the level of authority of the understudies. Maybe the motivation behind learning is to dominate the substance of the subject. The pertinence of instructing materials to day to day existence and how to utilize these training materials to tackle issues in life have gotten less consideration. The improvement of the curriculum that is currently being developed, especially Character Education which is processed by experts, can of course be accompanied by the active role of the government. This of course must bring up solution ideas from various parties in order to answer the development of global currents. It is common to see that at this time we are experiencing a decline in our identity as well as the concept of morals and mentality of an original nation's ideology. In reality, there are many kinds of shows of acts of violence, uncharacteristic behavior by the media which are ravaged by unrestrained freedom. This is very striking what is currently happening in our beloved nation. Character education is appropriate to restore the personality values of every citizen, but it must be appreciated by all parties even though the results will be achieved after one generation